A Patient-Centered, Provider-Facilitated Approach to the Refinement of Nonlinear Frequency Compression Parameters Based on Subjective Preference Ratings of Amplified Sound Quality - Johnson, Earl E.; Light, Keri C. (Journal of the American Academy of Audiology, 2015)
Purpose: To evaluate sound quality preferences of participants wearing hearing aids with different strengths of nonlinear frequency compression (NFC) processing versus no NFC processing. Two analysis methods, one without and one with a qualifier as to the magnitude of preferences, were compared for their percent agreement to differentiate a small difference in perceived sound quality as a result of applied NFC processing.Research Design: A single-blind design was used with participants unaware of the presence or strength of NFC processing (independent variable). The National Acoustic Laboratories-Nonlinear 2 (NAL-NL2) prescription of amplification was chosen because audibility is intentionally not prescribed in the presence of larger sensorineural hearing loss thresholds. A lack of prescribed audibility, when present, was deemed an objective qualifier for NFC. NFC is known to improve the input bandwidth available to listeners when high-frequency audibility is not otherwise available and increasing strengths of NFC were examined. Experimental condition 3 (EC3) was stronger than the manufacturer default (EC2). More aggressive strengths (e.g., EC4 and EC5), however, were expected to include excessive distortion and even reduce the output bandwidth that had been prescribed as audible by NAL-NL2 (EC1).Study Sample: A total of 14 male Veterans with severe high-frequency sensorineural hearing loss.Data Collection and Analysis: Participant sound quality preference ratings (dependent variable) without a qualifier as to the magnitude of preference were analyzed based on binomial probability theory, as is traditional with paired comparison data. The ratings with a qualifier as to the magnitude of preference were analyzed based on the nonparametric statistic of the Wilcoxon signed rank test.Results: The binomial probability analysis method identified a sound quality preference as well as the nonparametric probability test method. As the strength of NFC increased, more participants preferred the EC with less NFC. Fourteen of 14 participants showed equal preference between EC1 and EC2 perhaps, in part, because EC2 showed no objective improvement in audibility for six of the 14 participants (42%). Thirteen of the 14 participants showed no preference between NAL-NL2 and EC3, but all participants had an objective improvement in audibility. With more NFC than EC3, more and more participants preferred the other EC with less NFC in the paired comparison.Conclusions: By referencing the recommended sensation levels of amplitude compression (e.g., NAL-NL2) in the ear canal of hearing aid wearers, the targeting of NFC parameters can likely be optimized with respect to improvements in effective audibility that may contribute to speech recognition without adversely impacting sound quality. After targeting of NFC parameters, providers can facilitate decisions about the use of NFC parameters (strengths of processing) via sound quality preference judgments using paired comparisons.
Keywords: amplification; frequency lowering; hearing aids; hearing loss; nonlinear frequency compression; paired comparison; sound quality; speech perception